2001
DOI: 10.1046/j.1468-3083.2001.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased density of Demodex folliculorum and evidence of delayed hypersensitivity reaction in subjects with papulopustular rosacea

Abstract: Although Demodex mites do not seem to be the cause of rosacea, they may represent an important cofactor, especially in papulopustular rosacea. Immunohistochemical findings suggest that a delayed hypersensitivity reaction, possibly triggered by antigens of follicular origin, probably related to D. folliculorum, may occur, stimulating progression of the affection to the papulopustular stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
1
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 18 publications
8
152
1
13
Order By: Relevance
“…In a study conducted in patients with papulopustular rosacea, the presence of D. folliculorum in follicle secretions was found in 90.2 % of patients and only 11.9 % of control samples. Additionally, histopathological examination of skin obtained from these patients revealed that the presence of Demodex mites was connected with severe perifollicular lymphocytary infiltration (Georgala et al, 2001).…”
Section: Role Of Demodex Mites In Human Skin Diseasementioning
confidence: 94%
“…In a study conducted in patients with papulopustular rosacea, the presence of D. folliculorum in follicle secretions was found in 90.2 % of patients and only 11.9 % of control samples. Additionally, histopathological examination of skin obtained from these patients revealed that the presence of Demodex mites was connected with severe perifollicular lymphocytary infiltration (Georgala et al, 2001).…”
Section: Role Of Demodex Mites In Human Skin Diseasementioning
confidence: 94%
“…A Demodex atkák az esetek többségében tünetekkel nem járó infesztációt okoznak (14), azonban fôleg idô-sebb korban, immunszupprimáltakban vagy elhúzódó lokalis corticosteroid kezelés után etiológiai szerepük lehet gyulladásos tünetek kiváltásában (10,16,18,21,22,27). Rosaceás és nem specifikus arci gyulladásos tünetekkel jelentkezô betegekben kifejezettebb Demodex kolonizá-ciót találtak (8,13,17) és az intra-és esetenként extrafollicularisan kimutatható atkák szerepét felvetették a rosaceában észlelt, CD4 sejtekbôl álló gyulladásos infiltrátum valamint a papulopustulosus és granulomatosus tünetek kialakulásában is (3,14,20,23), azonban egyértelmû kór-oki szerepük nem igazolódott (9,23).…”
Section: Megbeszélésunclassified
“…Rosaceás és nem specifikus arci gyulladásos tünetekkel jelentkezô betegekben kifejezettebb Demodex kolonizá-ciót találtak (8,13,17) és az intra-és esetenként extrafollicularisan kimutatható atkák szerepét felvetették a rosaceában észlelt, CD4 sejtekbôl álló gyulladásos infiltrátum valamint a papulopustulosus és granulomatosus tünetek kialakulásában is (3,14,20,23), azonban egyértelmû kór-oki szerepük nem igazolódott (9,23). Szintén megnöve-kedett Demodex számot találtak perioralis dermatitisben, Grover-betegségben, eosinophil folliculitisben, papulopu- (11,24,25).…”
Section: Megbeszélésunclassified
“…Sağlam deride, kıl foliküllerinde, meibomian bezlerinde bazen hiçbir patojen etki yapmadan kalabildiği halde, deri temizliğinin iyi yapılmadığı hallerde, immün sistemin baskılandığı durumlarda patojen olabilmekte, inflamatuar dermatit yapabilmekte, keratoz ve epitelioma gelişi-mine katkıda bulunabilmekte, akne ve akne rozase oluşturabilmektedir. [3][4][5][6][7] Demodex spp taşıyan kirpiklerle yapılan kültürlerde Staphylococcus albus'un ürediği bildirilmiştir. Bazen kuvvetli deri reaksiyonlarına ve belirgin pigmentasyona neden olabilmektedir.…”
unclassified